Autism Spectrum Disorders and The Development of Children’s Aritmetic Aptitude and Numeracy - Arizkylia Yoka Putri; Kemil Wachidah (Mimbar Ilmu, 2023)
Initial numeration is part of the math skills that every student must have. However, children with autistic disorder do not have good initial numeracy skills. This study aims to analyze the initial numeracy abilities of students with autistic disorders. This research is case study research. The subjects of this study were 2 students with autistic disorder class III, namely boys and girls. Data collection techniques used in this study used interviews, observation, and test sheets related to the initial numeracy skills of students with autistic disorders. Data analysis techniques are carried out through several stages, namely data collection, data reduction, data display, and making conclusions. The results showed that D could recognize limited numbers in units 1-9 independently and could add and subtract limited units with assistance. N has not been able to recognize numbers and perform simple arithmetic. However, N can imitate writing unit numbers. The inability to master initial numeracy in students with autistic disorder is dominated by limited interest and attention, as well as brain disorders that cause low speech and language skills that impact numeracy mastery or recognition. So the teacher has an important role in improving his initial numeracy skills.